Analysis of higher order RNA structures in the influenza a virus genome - Dadonaite, B (2018)
Influenza viruses are respiratory pathogens, which constitute a major threat to public health. Up to 650,000 deaths and 5 million severe cases caused by seasonal influenza strains are recorded each year and potential pandemic influenza outbreaks pose a constant risk to the human population worldwide. Influenza viruses belong to the family Orthomyxoviridae and contain single stranded negative sense segmented RNA genomes. Each viral genome segment is maintained in a viral ribonucleoprotein complex (vRNP), which consists of the viral polymerase, oligomeric nucleoprotein and the viral RNA (vRNA). Little is known about the conformation of the vRNA in the context of the vRNP, although it has been proposed that secondary RNA structures in the vRNPs are essential for successful packaging of the influenza virus genome. The aim of the work presented in this thesis was to analyse the global secondary RNA structure of the influenza virus genome. To this end selective 2'-hydroxyl acylation analyzed by primer extension and mutational profiling (SHAPE-MaP) method was used to perform secondary RNA structure analysis on naked and vRNP-associated vRNA. The analysis showed that multiple secondary RNA structures are present in the genomes of influenza viruses, each vRNA segment has a unique secondary RNA structure fold, and no clear NP binding footprint was observed in the SHAPE reactivities. The presence of the structured vRNA sites suggested that some secondary RNA structures may be accessible to form interactions between vRNPs, therefore, further analysis using sequencing of psoralen crosslinked, ligated, and selected hybrids (SPLASH) was performed to detect inter-segment RNA-RNA interactions. A redundant network of RNA-RNA interactions was detected to be present inside influenza virions and mutagenesis work was performed to show that disruption of inter-segment RNA interactions can lead to defects in the virus genome packaging and attenuated virus growth. The relevance of this work to the reassortment between different influenza strains and the emergence of new pandemic strains is discussed.